Changing Trends from Traditional to Technology Based Approach - Nadir Ali (Linguistics and Literature Review, 2018)
Aphasia is an acquired neurological disorder of communication with a range of language impairments. Aphasia rehabilitation is becoming an important concern in clinical aphasiology. Traditional approaches for rehabilitation are being practiced. In addition to this, computer-based strategies are also employed in aphasiology. In this study, a qualitative phenomenological research approach is used to gain an understanding on how the SLPs of Pakistan perceive the changing trends of clinical practice in aphasia towards technology-based treatment method. This study presents lived experiences and preferences of the SLPs regarding changing trends from the traditional approach to the technology-based method. Ten SLPs participated and were recruited through purposive sampling. The participants were included if they were qualified SLPs and had at least 2 years of experience. The data was collected through audiotapes of detailed group discussions with the participants. The data was analyzed by using thematic analysis. The findings were grouped into five themes: traditional rehab activities, auditory and visual input, cost-effective approach, access and prognosis note. A range of sub-themes were also identified. The findings suggest the SLPs’ preferences are showing limited trends towards adapting the technology-based method.